Features principles and purposes of teacher performance evaluation. - Esnares José Maussa Díaz (Praxis, 2015)
Teacher evaluation represents a nodal aspect for improving of system education. Any evaluation has a previously predefined purpose and is essentially a valorative act, where the principles applied are indicators of the degree of responsibility which is performed and the visión that society gives to the education. This paper analyzes how the purposes are fulfilled, principles and characteristics of the performance evaluation of teachers in connection with the practice of respect for the guiding principles of assessment practice teaching; just like existing rating on indicators of professional and personal development achieved by teachers as a result of the evaluative practices in the context of the pursuit of improving of quality of education.